First Report of Plumeria Rust, Caused by Coleosporium plumeriae, in Thailand - TO-ANUN, CHAIWAT; VISARATHANONTH, NIPHON; ENGKHANINUN, JINTANA; KAKISHIMA, MAKOTO (Tropical Natural History, 2004)
Coleosporium plumeriae Pat. is a rust fungus (Melampsoraceae) found on Plumeria species. The disease is characterized by the formation of powdery, bright yellow-orange, erumpent, hypophyllous, punctiform uredinia on the abaxial portion of the leaf. The spermagonial and aecial states are unknown. Urediniospores are subglobose to angular, catenulate, coarsely verrucose with bluntly capitate, annulate tubercles, germ pores unconspicous, two or four, scattered. Lesions on the adaxial surface consist of minute spots with yellow color turning brown with age. This is the first report of a rust disease attacking leaves of Plumeria acuminata Ait. in Thailand.